Influence Analysis of Convective Heat Transfer of Circular Tubes and Flat Plates in a Polar Environment - Dongwei, Yu; Zhibing, Liu; Gang, Wu; Xueyang, Han; Guojun, Wang; Dayong, Zhang (Frontiers in Energy Research, 2022)
Electric heating serves as a major cold-proof measure because engineering equipment often loses efficacy in harsh weather conditions in a polar environment. Because Convective heat transfer is the key issue to solve the cold-proof design, this paper analyzes convective heat transfer of tube and plate in the constant heat flow heating mode. According to fluent numerical simulation analysis with a wind speed of 0–40 m/s and a temperature of −40°C–0°C, both an increase in wind speed and a decrease in temperature would cause the growth of the convective heat transfer coefficient of circular tubes and flat plates, Wind speed displayed a more significant impact on convective heat transfer. In a low-temperature laboratory, a model experiment of convective heat transfer was carried out to validate the reliability of the numerical simulation. Last, a prediction model for convective heat transfer coefficient of circular tubes and flat plates in polar environment was developed using numerical and experimental data.